Discourses of 'service delivery protests' in South Africa: an analysis of talk radio. Issue 2 (4th March 2021) - Day, Sarah; Cornell, Josephine; Malherbe, Nick
ABSTRACT: Although dominant discourses of various kinds are frequently reproduced on talk radio, the fundamentally collaborative nature of the medium also means that it is able to serve as a channel through which to challenge these discourses. Using Critical Discourse Analysis, this article examines how neoliberal ideology structures discussions around 'service delivery protest' on South African talk radio, and explores some of the roles that talk radio is, and is not, able to play in constructing resistance to neoliberal ideology. Our analysis yielded two discourses, namely: naturalisation of the commodification of everyday life, and market over welfare – both of which seemed to cohere with neoliberal frameworks and rationalities in different ways. We conclude by suggesting how radio can be used to denaturalise neoliberalism's impulse towards making common sense conditions that enable economic oppression and exploitation.